Implementation of Storytelling Through Powerpoint in Indonesian Language Learning to Import Student's Speaking Skills Sixth Grades Elementary School - Karimah, Dewi; Yuliyanto, Aan; Rogibah; Amaturrakhmah, Isna; Diningrat, Satya Raga; Meilani, Rifdha Regina (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2024)
Speaking skills include those that are not easy and simple, either for a teacher or for a student. Careful study and consideration are needed for speaking skills. At the Indonesian school performance, Indonesian education has not yet had optimal results, particularly in improving speaking skills. Like, students feel scared and nervous when they want to talk or communicate in front of their classmates. The literacy study aims to analyze the storytelling model through PowerPoint media on speaking skills in the Indonesian sixth-grade elementary class. The storytelling model is an interactive learning model because it emphasizes the active involvement of learners during the learning process. Thus, the storytelling model could be a reference to improving a student's speaking skills in Indonesian learning; a storytelling model through PowerPoint will hopefully attract the student's learning, thus improving their speaking abilities.